Aging exacerbates cardiac dysfunction and mortality in sepsis through enhancing TLR2 activity - Zhai, Yufeng; Yao, Qingzhou; The, Erlinda; Ao, Lihua; Fullerton, David A.; Meng, Xianzhong (Frontiers in Cardiovascular Medicine, 2023)
Introduction Sepsis is prevalent in the elderly population with increased incidence and mortality. Currently, the mechanism by which aging increases the susceptibility to sepsis and worsens outcome is unclear. We tested the hypothesis that aging exacerbates cardiac dysfunction in sepsis through a Toll-like receptor 2 (TLR2)-dependent mechanism. Methods Male young adult (4–6 months) and old (18–20 months) wild type (WT) and TLR2 knockout (KO) mice were subject to moderate sepsis by cecal ligation and puncture. Additional groups of young adult and old WT mice were treated with TLR2 agonist Pam3CSK4. Left ventricle (LV) performance was evaluated with a pressure-volume microcatheter. Tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6 and monocyte chemoattractant protein-1 (MCP-1) in the myocardium and plasma were assessed using enzyme-linked immunosorbent assay. Results Sepsis reduced LV ejection fraction and cardiac output in both young adult and old WT mice. However, identical CLP caused more severe cardiac dysfunction and high mortality in old WT mice that were accompanied by greater levels of TNF-α, IL-1β, IL-6 and MCP-1 in the myocardium and plasma. TLR2 KO diminished aging-related difference in myocardial and systemic inflammatory response, resulting in improved cardiac function and decreased mortality in old septic mice. In addition, higher myocardial TLR2 levels in old WT mice resulted in greater myocardial inflammatory response and worse cardiac dysfunction following administration of TLR2 agonist. Conclusion Moderate sepsis results in greater cardiac dysfunction and significant mortality in old mice. Aging elevates TLR2 level/activity to exacerbate the inflammatory response to sepsis, leading to worse cardiac dysfunction and mortality.